Half yearly report on outreach phase - II - BRAC (© BRAC, 2016)
1. Introduction 2. Coverage 3. Organizational Structure 4. Programme Inputs 5. Functional education 6. Training 7. Meeting & workshop 8. Resource mobilization 9. Internal Resource 10. External Resource 11. Economic Activities 12. Major sectoral activities 13. Consumption Loan 14. Women and Development 15. Credit Operation and women Programmes 16. Conclusion 16. Financial statement.